The Strategies Timeline and Activities Reporting Tables: Improving HIV Care by Improving the Reporting of Implementation Strategies - Garner, Bryan R; Bouris, Alida; Charlebois, Edwin D; Li, Dennis H; Dakin, Andrea; Moskowitz, Judith; Benbow, Nanette; Christopoulos, Katerina; Hickey, Matthew D; Imbert, Elizabeth (Journal of acquired immune deficiency syndromes (1999), 2025)
The United States has made significant progress toward achieving the goals of its Ending the HIV Epidemic initiative. However, systematic reviews on HIV implementation research have identified problems regarding strategy specification that limit the research's transparency and replicability, and in turn limit improvements regarding HIV care in real-world practice. The strategies timeline, activities, and resources (STAResources) Table, developed as part of the substance abuse treatment to HIV Care II Project, was completed for it and 3 other HIV implementation research projects funded by the National Institute of Health. Each evaluated it in terms of the extent to which it addressed prior recommendations on strategy specification; issues related to rigor and reproducibility; and the extent to which it seemed pragmatic, simple, adaptable, relevant, helpful, useful, acceptable, appropriate, suitable, applicable, and fitting. Each was rated on a 4-point scale (0 = not at all; 1 = a little; 2 = moderately, and 3 = very much). Overall, the STAResources Table was rated favorably. It received a mean of 3.0 (SD = 0) in terms of being pragmatic, relevant, helpful, acceptable, appropriate, and applicable. The Strategies Timeline, Activities, and Rationale (STARationale) Table emerged during the process and was also rated favorably. To help the Ending the HIV Epidemic initiative achieve its goals, there is a critical need for transparent and replicable implementation research on identifying the most effective strategies for equitably implementing evidence-based practices within real-world settings. Addressing this need, the Strategies Timeline and Activities Reporting (STAReporting)Tables are pragmatic tools for helping improve the transparency and replicability of implementation strategy research.